2020
DOI: 10.1109/access.2020.3041715
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Different BPD Placement Topologies for Shaded Modules in a Series-Parallel Configured PV Array

Abstract: This paper investigates the electrical performance of serial-parallel (SP) electric connections under artificial arrangement for partial shading conditions (PSCs) in a photovoltaic (PV) array. The concept of bypass diode (BPD) is a very attractive solution to reduce the shading effect on the PV module and therefore gives better performance in such shading environment types. Various bypass diode integration (BPD) placement topologies with the solar photovoltaic (PV) modules are being investigated to demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A detailed experimental study has been conducted using the proposed ken-ken puzzle-based reconfiguration technique of 4x4 PV array as shown in Fig. 18 Overall, comparative analysis of the reconfiguration methods are reported in Table 5. From the Table 5, it is observed that the KK configuration has reduced the shading loss by dispersing the occurrence of the shade uniformly throughout the array and improves the power generation with reduced complexity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed experimental study has been conducted using the proposed ken-ken puzzle-based reconfiguration technique of 4x4 PV array as shown in Fig. 18 Overall, comparative analysis of the reconfiguration methods are reported in Table 5. From the Table 5, it is observed that the KK configuration has reduced the shading loss by dispersing the occurrence of the shade uniformly throughout the array and improves the power generation with reduced complexity.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) The adaptive reconfiguration technique consists of a fixed bank and an adaptive bank. The modules in the fixed bank are connected in TCT configuration and remain static, whereas the adaptive bank is reconfigurable by employing a switching matrix to obtain uniform row current [16][17][18]. The dynamic configuration requires algorithms, switching matrix, and sensors that increase the complexity in the case of a largescale PV system and economically not feasible for the small-scale PV system.…”
Section: Introductionmentioning
confidence: 99%
“…The connection of PV is also essential. Series and parallel connections depend on the design of such applications [55]. Using a bypass diode is very important to protect the PV panel and reduce the shading effect to improve the overall efficiency [56].…”
Section: B Significant Of Maximum Power Point Trackingmentioning
confidence: 99%
“…This section presents a comprehensive explanation for the conventional PV system and problems thereof. The series-parallel PV array configuration is the most commonly used PV array structure due to its economical, practical and user-friendly features [17]- [19]. As an example, the conventional PV system is provided in Fig.…”
Section: Theoretical Analysis Of a Pv Array System A Conventional Pv ...mentioning
confidence: 99%